2009
DOI: 10.29333/ejgm/82660
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-pathological Assessment of Hysterectomies in Zaria

Abstract: Aim: To assess and compare accuracy of the clinical indications and histopathological diagnoses from hysterectomy specimens in Zaria. Methods The clinical indications comprised non-neoplastic-47 (14.8%) and neoplastic-226 (71.3%) causes. The commonest benign neoplastic indication was uterine fibroid 196 (61.8%). Malignant neoplastic indication included cervical cancer 12 (3.8%) and endometrial cancer 6 (1.9%). Cervical intraepithelial neoplasia (CIN), a preneoplastic lesion accounted for 44 (13.9%). Histopatho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Correlation between clinical and histological pattern is important in the general management of the patients. Studies done in India, Bangladesh and Nigeria found the correlation between pre-operative clinical and histological diagnoses were 74, 77 and 95.6% respectively [11,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Correlation between clinical and histological pattern is important in the general management of the patients. Studies done in India, Bangladesh and Nigeria found the correlation between pre-operative clinical and histological diagnoses were 74, 77 and 95.6% respectively [11,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…18.3% of cases had cystic ovaries and 9.2% had adenomyosis. Red degeneration is due to tumour vessel thrombosis and is associated with pregnancy and contraceptive use [10,11]. Further study on a larger sample size can be conducted to increase the power of the study.…”
Section: Resultsmentioning
confidence: 99%
“…In relation to fibromyoma, Buambo-Bamanga et al [10] in Congo Brazzaville in 2009, Yonli [7] in 2010 and Bambara in 2015 in Burkina Faso [8], Modupeola et al [14] in Nigeria in 2009 reported frequencies of 63.9%, 63.8%, 51.1% and 61.8% respectively.…”
Section: Discussionmentioning
confidence: 99%